Probing weak chemical interactions of metal surface atoms with CO-terminated AFM tips identifies molecular adsorption sites - Jalmar Tschakert; Qigang Zhong; Alexander Sekels; Pascal Henkel; Jannis Jung; K. Linus H. Pohl; Hermann A. Wegner; Doreen Mollenhauer; André Schirmeisen; Daniel Ebeling (Nature Communications)
Abstract Metal surfaces play a key role in on-surface synthesis as they provide a two-dimensional catalytic reaction environment that stimulates activation, diffusion, and coupling of molecular reactants. Fundamental understanding of the interactions between surface atoms and reactants is very limited but would enable controlling on-surface reaction processes for designing functional nanomaterials. Here, we measure chemical interactions between CO-terminated tips and Cu(111), Ag(111), and Au(111) surface atoms in all spatial directions with picometer resolution via low temperature atomic force microscopy. This allows a site-specific quantification of the weak chemical interactions of densely packed metal surface atoms and provides a picture of the potential energy landscape experienced by adsorbed reactants. Accompanying density functional theory calculations and the crystal orbital overlap population method reveal small covalent binding contributions from orbital overlap of the corresponding p- and d-states of the CO tip and the metal surface atoms as the cause for the site-specific interactions. Accessing such small covalent bonding contributions in the background of the dispersion-dominated interaction enables revealing insights into the nature of chemical bond formation with metal surface atoms and a reliable determination of molecular adsorption sites. The latter can serve both as a starting point and as a direct comparison with theoretical studies.